Ruthenium trisbipyridine as a candidate for gas-phase spectroscopic studies in a Fourier transform mass spectrometer. Issue 2 (2004) - Scott Scott, Jill R. Jill R.; Ham Ham, Jason E. Jason E.; Durham Durham, Bill Bill; Tremblay Tremblay, Paul L. Paul L.
Abstract : Metal polypyridines are excellent candidates for gas-phase optical experiments where their intrinsic properties can be studied without complications due to the presence of solvent. The fluorescence lifetimes of [Ru(bpy)3 ] 1+ trapped in an optical detection cell within a Fourier transform mass spectrometer were obtained using matrix-assisted laser desorption/ionization to generate the ions with either 2, 5-dihydroxybenzoic acid (DHB) or sinapinic acid (SA) as matrix. All transients acquired, whether using DHB or SA for ion generation, were best described as approximately exponential decays. The rate constant for transients derived using DHB as matrix was 4×10 7 s −1, while the rate constant using SA was 1×10 7 s −1 . Some suggestions of multiple exponential decay were evident although limited by the quality of the signals. Photodissociation experiments revealed that [Ru(bpy)3 ] 1+ generated using DHB can decompose to [Ru(bpy)2 ] 1+, whereas ions generated using SA showed no decomposition. Comparison of the mass spectra with the fluorescence lifetimes illustrates the promise of incorporating optical detection with trapped ion mass spectrometry techniques.